Analysis of Web Server Security Challenges - E. C., Amadi; F. C., Onenunne; O. C. , Iheukwumere; U. N. , Onyeyiri (International Journal For Research In Advanced Computer Science And Engineering, 2016)
As the web expands in size and adoption, so does the interest of attackers who seek to exploit web applications and infiltrate user data. While there is a steady stream of news regarding major breaches and millions of user credentials compromised. It is logical to assume that overtime, the applications of bigger players of the web are becoming more secure. However as these applications become resistant to most prevalent attacks, adversaries may be tempted to move easier, unprotected target would still hold sensitive user data. This article reviews some of the security challenges being faces by web server on the internet.